2019
DOI: 10.1007/s10064-019-01632-w
|View full text |Cite
|
Sign up to set email alerts
|

The “Salcher” landslide observatory—experimental long-term monitoring in the Flysch Zone of Lower Austria

Abstract: Shallow landslide processes in geologically prone areas are recognised to pose threat to both human life and property. As precipitation is one of the main triggers for landslides, hydro-meteorological interrelationships and related future changes regarding frequency and magnitude of landslide processes in particular are of major interest. Long-term monitoring investigations of active landslide sites can provide a better understanding of the kinematic behaviour and triggering conditions of slope instabilities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Taking into account relation (6) and assuming the observation point normal to the side of the cylinder, we get:…”
Section: Electric Double Layermentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account relation (6) and assuming the observation point normal to the side of the cylinder, we get:…”
Section: Electric Double Layermentioning
confidence: 99%
“…It is observed that landslide activity is associated with long-term meteorological events, such as rainfall [4]. The traditional method used for years to track landslide movements is the inclinometer method [5,6]. However, most methods monitor the landslide process in discrete moments of time or give information about the movement of a landslide when catastrophic movement begins.…”
Section: Introductionmentioning
confidence: 99%